Financial Resource Curse in Resource-Rich Countries - Mlachila, Montfort (IMF Working Papers; Working Paper ;, 2017)
Why do commodity-dependent developing countries have typically lower levels of financial development than their peers? The literature has proposed many possible explanations, but it typically does not dwell on the deep mechanisms that drive such an outcome. In this paper, we argue that the main cause is the shocks in commodity prices. We test the hypothesis on 68 commodity-rich developing countries between 1980 and 2014, and we find strong evidence of the financial development resource curse through the channel of commodity price shocks, after controlling for other explanations found in the literature. The findings are robust to the different types of commodities, the nature of the shocks, and various indicators of financial development. We also show how the impact of these shocks can be mitigated through good quality of governance.